The utility of water leak test in evaluating the functionality of sterilization containers - DAOUDI, Hajar; ARBAI, Soumaya; EL MARNISSI, Safaa; EL HARTI, Jaouad; DERRAJI, Soufiane; AIT EL CADI, Mina (Jour Med Resh and Health Sci, 2023)
Introduction: The reprocessing of reusable medical devices is a specialized process that requires careful management and control of various preparation steps [1]. The sterile state of a medical device can only be maintained when the integrity of the sterile barrier is not compromised [2]. Materials & Methods: This study employed a prospective descriptive observational design. An inventory was conducted to list all the containers used in the visual integrity check process and water leak test.The detection of a leak necessitated the replacement of the container's seal. If the leak persisted, the entire container was replaced. Results & Discussions: The results of the water leak test showed that out of the 55 tested containers, 25 were positive, indicating a positivity rate of 45% and requiring maintenance or replacement interventions. Comparing the results revealed significant differences in the positivity rates, ranging from 8% to 28%, which can be attributed to variations in technical and educational resources among different facilities. Conclusion: Our findings highlight the need for corrective actions, such as personnel training on proper usage, maintenance, and regular systematic inspection of the containers. Additionally, developing instructions for proper packaging and sealing is essential to address the identified issues.